2021
DOI: 10.1002/pc.26139
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior and dielectric response of epoxy–boron nitride composites reinforced with short human hair fiber

Abstract: Polymer composites with low dielectric constant and high thermal conductivity are gaining considerable attention due to their rising demand in various microelectronic applications such as printed circuit boards, connectors, encapsulations, and electrical contacts. In the present investigation, thermal and dielectric properties of a new class of epoxy-based hybridized composites with improved thermal conductivity (k), high glass transition temperature (T g ), low coefficient of thermal expansion (CTE), controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…[14] Besides high T g , high thermal conductivity and low coefficient of thermal expansion of EPs are always desired for their industrial applications, especially from an electronic packaging perspective. To date, considerable efforts have been made to improve the heat endurance and heat dissipation capabilities of EP-based dielectric materials by inorganic particle doping [15][16][17][18][19][20][21][22][23][24] and chemical modification. [25][26][27] Furthermore, EP is also an indispensable adhesive that is extensively used in power equipment.…”
mentioning
confidence: 99%
“…[14] Besides high T g , high thermal conductivity and low coefficient of thermal expansion of EPs are always desired for their industrial applications, especially from an electronic packaging perspective. To date, considerable efforts have been made to improve the heat endurance and heat dissipation capabilities of EP-based dielectric materials by inorganic particle doping [15][16][17][18][19][20][21][22][23][24] and chemical modification. [25][26][27] Furthermore, EP is also an indispensable adhesive that is extensively used in power equipment.…”
mentioning
confidence: 99%
“…Under this circumstance, epoxies filled with high thermal conductive fillers are emerging as a cost‐effective way to cope with thermal management issues. Incorporating highly thermally conductive ceramic fillers in polymers have long been studied to improve the thermal conductivity of the composites 4–8 . In these composite systems, the filler size and content have been reported to be major factors affecting thermal conductivity, where efficient packing could increase the loading density of the fillers in the polymer matrix 9–14 .…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating highly thermally conductive ceramic fillers in polymers have long been studied to improve the thermal conductivity of the composites. [4][5][6][7][8] In these composite systems, the filler size and content have been reported to be major factors affecting thermal conductivity, where efficient packing could increase the loading density of the fillers in the polymer matrix. [9][10][11][12][13][14] Research on their applications has shown that high filler loading (>70 wt%) is still the main method to obtain high thermal conductivity of epoxy insulation packaging materials for electrical equipment.…”
mentioning
confidence: 99%
“…Hexagonal boron nitride (h-BN) nanosheets, as a promising 2D ceramic material, have several advantages over both carbon-based materials and metal nanoparticles, including high thermal stability, [13] excellent corrosion resistance, [6] outstanding oxidize resistance, [14] and excellent electrical insulation, [15] rendering it an exceptional thermal conductive filler for enhancing the heat transfer performance of polymers. [16,17] Nevertheless, the lack of active groups causes BN to clump together and distribute poorly in the polymer matrix, forming many interfacial thermal resistances (ITR) between the filler and the matrix, as well as the overlaps of fillers. [18,19] To solve these problems, surface functionalization can ameliorate the interfacial affinity of BN.…”
Section: Introductionmentioning
confidence: 99%